Online technology: sustainable higher education or diploma disease for emerging society during emergency—comparison between pre and during COVID-19 - Alam, Gazi Mahabubul; Asimiran, Soaib (Elsevier, 2021)
Even as the pandemic rages on across the globe, the notion of shutting down higher education has never been an option; instead, finding ways to circumvent it has led to a greater reliance on online technology delivery of courses and programs. Although this is not meant as a complete substitute, critics argue that online education has widened the ‘diploma disease’ crisis. They argued that this would lead to serious long-term problems which may become irreversible. This comparative study was conducted using an ‘empirical survey’ with 120 students from each group (before and during COVID-19, giving a total of 240 samples/students) to conduct an in-depth study of the academic and job-ready performance of graduates. Findings show that pre-pandemic students did poorly academically compared to during-pandemic counterparts. On the other hand, pre-pandemic graduates achieved better job-readiness scores which included both aptitude and practicum. Moreover, both groups achieved well in terms of academic performance compared to their job-readiness scores. This leads to the question: is it the role of HE to value the concept of sustainable production or to produce certificates/qualifications? Apparently, the HE system has used COVID-19 as an excuse to extend the “diploma disease crisis”, a situation that must be addressed by devising a proper policy framework.